BAYESIAN ANALYSIS FOR THE BURR TYPE XII DISTRIBUTION BASED ON RECORD VALUES - Nadar, Mustafa; Papadopoulos, Alexandros (Univ Studi Bologna, Dipt Scienze Statistiche Paolo Fortunati, 2011)
In this paper we reviewed and extended some results that have been derived on record values from the two parameters Burr Type XII distribution. The two parameters were assumed to be random variables and Bayes estimates were derived on the basis of a linear exponential (LINEX) loss function. Estimates for future record values were derived using non Bayesian and Bayesian approaches. In the Bayesian approach we reviewed the estimators obtained by Ahmedi and Doostparast (2006) using the well known squared error loss (SEL) function and we derived estimate for the future record value under LINEX loss function. A numerical example with tables and figures illustrated the findings.